Burden of Neurological Diseases in Peru 1990-2015: A Systematic Analysis of the Global Burden Disease 2015 - Pacheco Barrios, Kevin (2018)
Introduction: Burden of diseases integrated mortality and disability and assess the impact of diseases on population. This study analyzes the burden of neurological diseases in Peru in 1990‐2015. Methods: We used the data published by the Institute for Health Metrics and Evaluation from 1990 to 2015. The measure of burden used was Disability‐adjusted life years (DALYs), the sum of the Years of Life Lost (YLL) and Years Lived with Disability (YLD). Data were selected for Peru in 1990 and 2015, per year, sex, age, and type of neurological disorder. Results: The total DALYs for neurological causes in Peru was 9.06% and 10.65% in 1990 and 2015, respectively. In 2015, the five main causes were: migraine; cerebrovascular disease (CVD); neonatal encephalopathy (NE), Alzheimer disease and other dementias (ADD), and medication overuse headache (MOH). Women contributed 54.16% of DALYs. Cancer of CNS and ADD showed the higher increase. The main cause of YLL and YLD was neonatal encephalopathy and migraine, respectively. Conclusion: The burden of neurological diseases increased 1.6% from 1990 to 2015. The main causes were: migraine, CVD, NE, ADD and MOH. Alzheimer disease and CNS cancer doubled the DALYs in this period. Priority actions should be taken to prevent and treat their causes.